Transformasi Digital dalam Manajemen Talenta: Analisis Praktik pada Perusahaan Startup Teknologi di Jakarta - Zuhrofi, Ahmad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Digital transformation has prompted various sectors, including the human resources sector, to adapt to increasingly dynamic technologies. Technology startups in Jakarta as innovation pioneers have a strategic role in implementing digital-based talent management. This study aims to examine the role of digital technology in talent management practices in technology startups with a literature study approach. Data is collected through literature review from various sources such as scientific journals, books, and current industry reports. The results of the study show that the use of digital technology, such as AI-based recruitment applications, performance management platforms, and online learning systems, is able to improve the efficiency of HR processes and create a more adaptive work experience for employees. However, challenges such as data security, organizational culture adaptation, and digital divide remain obstacles to optimal implementation. This research provides a conceptual overview and strategic implications for the development of digital talent management in the Indonesian startup sector.